Pelatihan Pembuatan Fodder Jagung bagi KTT Andini Lestari Kecamatan Karanganyar Kabupaten Karanganyar - Yuli Yanti; Muhammad Muna Ramdani; Rafif Hilmi Nugroho; Rhifdhi Naufal Rakhman; Rika Nur Laila; Rizvanda Akbar Muhamad; Saddam Firdaus; Sastiya Dwitasari; Shipa Amalia Saputri; Syafira Nur Azizah; Yesi Sabela (Universitas Sebelas Maret, 2026)
Training on Corn Fodder Production for the KTT Andini Lestari, Karanganyar District, Karanganyar Regency. The availability of land for growing green fodder is currently still a challenge in meeting the need for green fodder, especially for beef cattle farmers. Some members of the Andini Lestari Livestock Farmers Group (KTT) have experienced this. The purpose of this activity was to provide technology transfer and training in making corn fodder at KTT Andini Lestari, Karanganyar, Central Java. The method used by MBKM (Merdeka Belajar Kampus Merdeka) students of the Universitas Sebelas Maret Animal Husbandry Study Program, Faculty of Animal Husbandry, was to provide counseling and training on planting corn fodder hydroponically using stacked racks. This training used a participatory methodology. The community service activity was divided into three stages: preparation, implementation, and monitoring and evaluation. Respondents' knowledge was measured with a pre-test and post-test with five questions. Corn fodder is a sprout from a corn plant that can be harvested at least 7 days to be used as green fodder for livestock. Hydroponic corn fodder harvested at 14 days old has a height of 15 cm. After the outreach and training, the 30 participants gained an average of 94.6% more knowledge about alternative feed, hydroponic corn fodder. Corn odder can be a solution to meet livestock feed needs with limited land availability, thus supporting the sustainability of the beef cattle business at the Andini Lestari Livestock Farmers Group (KTT) in Lalung Village, Karanganyar.